2023
DOI: 10.1186/s40478-023-01575-0
|View full text |Cite|
|
Sign up to set email alerts
|

Retina-to-brain spreading of α-synuclein after intravitreal injection of preformed fibrils

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the aggregation of misfolded α-synuclein and progressive spreading of the aggregates from a few discrete regions to wider brain regions. Although PD has been classically considered a movement disorder, a large body of clinical evidence has revealed the progressive occurrence of non-motor symptoms. Patients present visual symptoms in the initial stages of the disease, and accumulation of phospho-α-synuclein, dopaminergic neuronal loss, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
1
3
1
Order By: Relevance
“…This observation suggests that α-Syn may not be highly susceptible to injury in the context of ONC. These findings contrast with the observed RGC loss and reduction in melanopsin-positive RGCs in PD models 59 and α-Syn overexpression in the retina 65 , 66 . This suggests that α-Syn positive RGCs may not be highly susceptible to traumatic injury but may be more vulnerable to chronic neurodegenerative processes associated with PD.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation suggests that α-Syn may not be highly susceptible to injury in the context of ONC. These findings contrast with the observed RGC loss and reduction in melanopsin-positive RGCs in PD models 59 and α-Syn overexpression in the retina 65 , 66 . This suggests that α-Syn positive RGCs may not be highly susceptible to traumatic injury but may be more vulnerable to chronic neurodegenerative processes associated with PD.…”
Section: Discussioncontrasting
confidence: 99%
“…It was interesting to note that olfactory neurons (particularly TH+ , periglomerular cells) were highly enriched for αSyn whereas retinal ganglion cells and amacrine cells expressed very low levels of αSyn, which bordered on the lower limit of detection. This is consistent with recent findings that suggest the olfactory bulb is likely a richer source of seed-competent αSyn than the retina however contrary to a 2016 study that found wildtype αSyn does not colocalize with TH+ cells in the periglomerular olfactory bulb 62 66 . This discrepancy may be due to the presynaptic/cytosolic localization of αSyn in wildtype mice whereby TH+ neurons in the periglomerular region of the olfactory bulb can project outside this layer, making interpretation of wildtype αSyn localization difficult.…”
Section: Discussionsupporting
confidence: 91%
“…Arguably, the CNS mainly needs to simulate inputs related to the most impaired sensory modality, whereas, for example the auditory side is less affected and, consequently, there is no need for hallucinations in order to speak. Indeed, alpha-synuclein has prion-like diffusion through the visual pathway and this could explain its preponderant and early involvement in LBD (since it is probably the starting point) and its later damage (according to Braak’s stages) in PD, justifying their different frequency and temporal sequence of visual hallucinations [ 15 ]. Furthermore, although LBD patients may also manifest parkinsonism due to dopaminergic alterations, this is not always present and is usually of lesser extent than in PD patients [ 14 ].…”
mentioning
confidence: 99%